2020
DOI: 10.7150/ijbs.42966
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ inhibition boosts efficacy of PD-L1 Checkpoint Blockade Immunotherapy against Murine Melanoma in a sexually dimorphic manner

Abstract: Immune checkpoint blockade-based immunotherapy has become standard of care for multiple cancer types. However, the overall response rates among various cancer types still remain unsatisfactory. There is a pressing clinical need to identify combination therapies to improve efficacy of anticancer immunotherapy. We previously showed that pharmacologic inhibition of PPARγ by GW9662 boosts αPD-L1 and αPD-1 antibody efficacy in treating murine mammary tumors. In addition, we defined sexually dimorphic αPD-L1 efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The activation of PPAR-γ displays a contradictory effect in immunotherapies equally. According to Wu, B., et al., the inactivation of PPAR-γ boosts the efficacy of αPD-L1 and αPD-1 antibodies in the treatment against murine mammary tumors ( 53 ). The activation of PPAR-γ in turn suppresses the expression and secretion of inflammatory factors, pro-inflammatory chemokines, which may reprogram the immune microenvironment of cancer to be less “inflamed”, consequently enabling resistance of cancer cells to immune-directed therapies ( 54 ).…”
Section: Functions Of Ppar-γmentioning
confidence: 99%
“…The activation of PPAR-γ displays a contradictory effect in immunotherapies equally. According to Wu, B., et al., the inactivation of PPAR-γ boosts the efficacy of αPD-L1 and αPD-1 antibodies in the treatment against murine mammary tumors ( 53 ). The activation of PPAR-γ in turn suppresses the expression and secretion of inflammatory factors, pro-inflammatory chemokines, which may reprogram the immune microenvironment of cancer to be less “inflamed”, consequently enabling resistance of cancer cells to immune-directed therapies ( 54 ).…”
Section: Functions Of Ppar-γmentioning
confidence: 99%
“…We previously reported sex differences in tumor growth in a PD-L1-dependent manner 23 and we found sex differences in other tumors based on obesity and additional factors. 24 Full understanding of sex differences aside from estrogen effects merit further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PPARα which promotes FA catabolism in T lymphocytes for effector functions, 40 PPARγ drives M2 macrophage polarisation and DC tolerisation by triggering FA oxidation. 47 48 Of note, both PPARγ agonist and antagonist have been shown to enhance anti-PD-(L)1 efficacy in cancer models, [49][50][51] which may depend on the CD274 trans-activation effect of PPARγ in different cell types. 49 51 In addition to anti-PD-L1 therapy, we found that cotargeting PPARγ with anti-PD-1 antibody can also counteract the adaptive resistance phenotype (data not shown).…”
Section: Hepatologymentioning
confidence: 99%